INFLUENCE OF INTERNET ADDICTION ON ACADEMIC PERFORMANCE OF SENIOR SECONDARY SCHOOL STUDENTS OF ISLAMIC STUDIES - Jibril Olaniyi Ayuba; Lawal Abiola Abdullateef (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
The study examined the influence of internet addiction on academic performance of senior secondary school Islamic Studies students in Ilorin, Nigeria. The study adopted quantitative method of research design. Simple random sampling technique was used to select 150 senior secondary school students of Islamic Studies in Ilorin, Nigeria. An adapted questionnaire was used to elicit information from the respondents. Two research questions were raised and answered using Mean and Standard Deviation while PPMC was used to test formulated hypothesis at 0.05 level of significance. Findings from the study revealed that there is high level of internet addiction among senior secondary school students of Islamic studies in Ilorin, Nigeria. Also, the study revealed that there is significant relationship between internet addiction and students` academic performance among senior secondary school students in Ilorin, Nigeria. In line with the findings of the study, it is recommended that schools should organize seminars for students to use internet to enhance academic excellence. It was concluded that teachers and parents must work together to assist the students on effective usage of internet usage.